PENDAMPINGAN HUKUM DAN PSIKOLOGIS TERHADAP MASYARAKAT KPM PKH DESA BRAJA HARJOSARI KECAMATAN BRAJA SELEBAH KABUPATEN LAMPUNG TIMUR TERHADAP KEKERASAN DALAM RUMAH TANGGA (KDRT) - Permatasari, Ermanita; Dewi Trismahwati; Siti Fatimah (LPPM STAI DARUSSALAM LAMPUNG, 2023)
Household integrity is the dream of every husband and wife. Building a family that is full of love, comfort and security is a manifestation of a happy family life. Violence that occurs in the household is indicated as a violation of human rights. Domestic violence is also a form of crime against human dignity. This is because domestic violence tends to lead to discriminatory behavior, where all forms of domestic violence cannot be justified. Thus, domestic violence behavior in any form can result in criminal charges and be processed legally. Community Service Activities carried out by the PKM STAI Darussalam Lampung Team were carried out in Braja Harjosari Village, Braja Selebah District, East Lampung Regency, is a service in the form of Assistance, Legal and Psychological Assistance for the KPM PKH Community, Braja Harjosari Village, Braja Selebah District, East Lampung Regency Against Internal Violence Household (KDRT). Based on the implementation of the service that has been carried out, it can be concluded that all participants participated in this activity enthusiastically. The knowledge they have is increasing. Both about the meaning of domestic violence, the impact of domestic violence and the legal umbrella for victims of domestic violence. Participants no longer consider domestic violence to be a disgrace to the victim's family. So that victims no longer feel afraid and embarrassed to report the violence they experience to people they trust.